NIR-sensitive UCNP@mSiO2 nanovehicles for on-demand drug release and photodynamic therapy. Issue 31 (11th March 2016) - Zhang, Ting; Lin, Huiming; Cui, Liru; An, Na; Tong, Ruihan; Chen, Yuhua; Yang, Chunyu; Li, Xin; Qu, Fengyu
Abstract : The synthesis of UCNP@mSiO2 /HA nanovehicle reveals the NIR-triggered chemotherapy/PDT as well as the enhanced specific cytotoxicity to cancer cell. Abstract : Nanocomposites have attracted the most attention for antitumor treatment. Here, we present a near-infrared (NIR) sensitive nanovehicle to reveal synergistic chemotherapy and photodynamic therapy (PDT). Upconverting nanoparticles (UCNP) NaYF4 :Yb, Tm@NaYF4 were adopted as the core using a one-step coprecipitation method to realize the coating of the mesoporous silica shell and the doping of photosensitizer Hypocrellin A (HA). Furthermore, a UV light-cleavable 4-(2-carboxy-ethylsulfanylmethyl)-3-nitro-benzoic acid linker (CNBA) was synthesized and grafted outside as a "gate" to insure the encapsulation of the anticancer drug doxorubicin (DOX). Upon NIR irradiation, the UV light emission (derived from UCNP) can induce the break of the CNBA linker to make the "gate" open and cause drug release. Besides, the blue emission (450–470 nm) can excite HA to generate reactive oxygen (ROS) to achieve PDT. Owing to the nanoscale particle size (75 nm) and targeting transferrin (Tf) modification, these nanocomposites possess fast uptake by cancer cells (HeLa and MCF-7) and the enhanced cytotoxicity is derived from the synergistic effect of chemotherapy and PDT that would easily be controlled by the acting strength and time of NIR irradiation. Hence, the NIR light-sensitive nanocomposites are expected to be the promising and flexible platform for cancer treatment.